Fundamentals of C++ and data structure - Lambert, Kenneth A.; Naps, Thomas (Singapore : Course Technology Cengage Learning, 2009)
Following the success of Fundamentals of Program Design and Data Structures by Lambert and Naps, C++ Advanced Course is essential for a second course in Computer Science. Completely updated, this text provides in-depth coverage to help students prepare for the AP exam, Exam AB. A full introduction to the essential features of C++ is provided and programming techniques are emphasized in the context of interesting and realistic case problems. This text is compatible with C++ compilers from Microsoft, Borland, and Metrowerks.
Unit 1: Software Engineering Principles Lesson 1: Algorithm Analysis: Space and Time Considerations Lesson 2: Data Abstraction and Object-Oriented Software Engineering Unit 2: Linear Data Structures Lesson 3: Linked Lists Lesson 4: Stacks and Queues Unit 3: Recursion and Recursive Data Structures Lesson 5: Recursion Lesson 6: Binary Trees, General Trees, and Graphs Unit 4: Advanced Sort and Search Algorithms Lesson 7: More Powerful Sorting Methods Lesson 8: More Powerful Search Methods Appendices A: Reserved Words B: Some Useful Library Functions C: Syntax Diagrams D: The ASCII Character Set E: Random Number Generation
Includes index.
Keywords: C++ (COMPUTER PROGRAM LANGUAGE)